Effectiveness of Carica Papaya Dry Seed as Natural Coagulants in Wastewater Treatment Process - Abdul Rahman Adrin, Muhammad Hakim; Ngadiman, Norhayati; Abdullah, Noorul Hudai; Mohd Hamsani, Nadira Nursani; Nasharuddin, Nisya; Omar, Noor Nufaiha (semarak ilmu, 2024)
This study aims to assess the efficacy of Carica papaya-dried seeds as a natural coagulant in the wastewater treatment process. Using natural coagulants in water treatment provides a safer and more sustainable method. Insufficient research in this field hinders a thorough comprehension of the ideal circumstances, dosage, and potential impacts of Carica papaya dry seed coagulation on pollutant elimination in wastewater. Therefore, the investigation of the extraction procedure for coagulants derived from dried Carica papaya seeds is essential to establish a reliable and efficient method suitable for use in wastewater treatment facilities. The number of experiments were conducted to accomplish the objective of this study. The experiment utilised textile effluent from an industrial area in Parit Raja, Johor as the wastewater sample. The Carica papaya seeds were ground into a powder and then mixed with Sodium Chloride (NaCl) and distilled water to create a coagulant solution. COD, turbidity, pH, and settling depth were measured to assess the effectiveness of Carica papaya seeds in treating the effluent sample. At a Carica papaya seed coagulant dosage of 2.0 mL with a NaCl concentration of 1.5 M, the optimal COD reduction and turbidity removal efficacy were at 20.95 % and 23.00 %, respectively. This study shows that among 5 different concentration solvent, 1.5M NaCl is most optimum concentration condition demonstrated. Moreover, the research represents the significant potential of Carica papaya seed powder as a natural coagulant for treating wastewater that contains textile colouring agents. In conclusion, the research demonstrated that dried Carica papaya seeds possess the potential to serve as a natural coagulant in wastewater treatment procedures, thereby presenting a safer and more ecologically sustainable alternative. This study offers insights into the ideal conditions for utilising dried Carica papaya seeds as a natural coagulant for treating wastewater that contains textile colouring agents.